2005
DOI: 10.1111/j.1539-6975.2005.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

The Simple Analytics of a Pooled Annuity Fund

Abstract: This paper provides a formal analysis of payout adjustments from a longevity risk-pooling fund, an arrangement we refer to as Group Self Annuitization (GSA). The distinguishing risk diffusion characteristic of GSAs in the family of longevity insurance instruments is that the annuitants bear their systematic risk, but the pool shares idiosyncratic risk. This obviates the need for an insurance company, although such instruments could be sold through a corporate insurer. We begin by deriving the payout adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 16 publications
3
103
0
Order By: Relevance
“…Only a limited number of studies has examined unit-linked annuities which allow the insurer to share investment and longevity risk with the policyholder (see, e.g., Piggott et al 2005;Denuit et al 2011;Richter and Weber 2011;Maurer et al 2013a). Based on those studies and our findings here, we believe that participating annuities offer retirees a favorable combination of access to the mortality credit and a smoothed payout stream for life.…”
Section: Resultssupporting
confidence: 58%
“…Only a limited number of studies has examined unit-linked annuities which allow the insurer to share investment and longevity risk with the policyholder (see, e.g., Piggott et al 2005;Denuit et al 2011;Richter and Weber 2011;Maurer et al 2013a). Based on those studies and our findings here, we believe that participating annuities offer retirees a favorable combination of access to the mortality credit and a smoothed payout stream for life.…”
Section: Resultssupporting
confidence: 58%
“…The Equitable experience demonstrated that the actuarial philosophy for surplus management and bonus policy along with the pricing and reserving for risks must take into account market risks and should take into account market consistent valuations of both assets and liabilities. An approach to using experience sharing to mitigate systemic adverse changes has also been proposed in Piggott, Valdez, and Detzel (2005). Risk sharing of extreme risks is a product feature that is potentially very valuable in the product design of life annuities.…”
Section: Longevity Risk Hedgingmentioning
confidence: 99%
“…The present proposal is related to the concept of Group Self-Annuitization (GSA), studied by Piggott, Valdez & Detzel (2005) and Valdez, Piggott & Wang (2006). The term Group SelfAnnuitization (GSA) is used to describe a group self-annuity plan which will allow retirees to pool together and form a fund in order to provide for protection against longevity.…”
Section: Introductionmentioning
confidence: 99%
“…The annuitants only bear the systematic part of the longevity risk, whereas the insurer covers the random fluctuation of mortality as well as the expected future mortality improvements and possible departures from the guaranteed interest rates. In the framework of Piggott, Valdez & Detzel (2005), Van de Ven & Weale (2008) discuss the way in which payments from pooled annuity funds need to be adjusted when future mortality rates are not known with certainty. They investigate "mortality adjusted" annuities in which aggregate mortality risk is transferred from the provider to the annuitants, allowing for the level of risk aversion of the annuitant.…”
Section: Introductionmentioning
confidence: 99%